Get it Done Now! - Tracy, Brian (Ascent Audio, 2020)
There is a quote attributed to that most famous of individuals, Anonymous, "Starve your distraction, and feed your focus." This is the perfect idea with which to open this great new work from Brian Tracy. We live in the most technologically advanced period of history, and in the most technologically advanced country. With the advent of mobile phones, killer apps, broadband internet speeds that stagger the imagination, and nearly any bit of information or products/solutions only one click away, how can it be that remaining optimally productive is such a challenge for so many? In a word: Distraction. Many of us spend precious time focusing on the incessant and numerous emails, texts, notifications, ads, etc. that seem important . . . even urgent . . . to our success and happiness, but in reality only complicate our lives and take us even further from our goals. Brian addresses this challenge of distraction in its many forms and shows you how to "feed your focus" on a daily basis. Learn: productivity promises and pitfalls in our modern age; the psychology of productivity; the best productivity methods ever conceived; how to end procrastination once and for all; and productivity and relationships: where it applies and where it doesn't.